O(a) professor(a) de ensino religioso e os(as) alunos(as) de 4ª e 5ª série do ensino fundamental : as relações de troca de saberes e de confiança no espaço educativo da sala de aula - Fortes, Gianice Stabile (2008)
This paper aims at analyzing the exchange of loyalty, affection and confidence between the Religion Education teacher and 4th and 5th graders (Elementary School) in the classroom of a Methodist school in Porto Alegre as all the aspects related to such interaction, having as a goal conscious and reflective growth of all those taking part in the process. Thus, in order to cover these aspects, this paper is organized in three chapters. The first one is about the teaching of Religion as a religious phenomenon and all the documents which refer to it. The second chapter draws on issues related to children and adolescents who are in the 4th and 5th grades connecting biopsychosocial, cognitive and religious aspects. The third chapter studies teacher s educational background and presents the results of the research. The methodology applied is the participative research. Three observations were made in a 4th grade morning group and three in an afternoon group, three observations were made in a 5th grade morning group and another three in an afternoon group. It is important to mention that the teachers work in different shifts. After the observations period, two questionnaires with semi-open questions were prepared and addressed to the teachers who were able to discuss the questions with the researcher. Another questionnaire with objective questions was prepared and addressed to the students who could only answer it under parents consent. Results were analyzed by the researcher and represented through the use of graphics.